Adubação nitrogenada na produção de biomassa e sementes de azevém em rotação com soja - Bohn, Alberto (2014)
The experiment was conducted at the Experimental Station of Embrapa Clima Temperado/Lowlands and Seed Analysis Laboratory of the Department of Plant Science, UFPel. Different densities in the soil seeds (T1 - 777.70 kg.ha-1; T2 - 736.63 kg.ha-1; T3 - 624.59 kg.ha-1 and T4 - 234.42 kg.ha-1) were tested in annual ryegrass (Lolium multiflorum Lam.) in succession to soybean crop. Forage harvesting has occurred twice and after the second defoliation, were tested different levels of urea (null; 45; 90 and 135 kg.ha-1). The highest densities produced more rapid crop establishment and greater mass of harvested forage, both at first and in the second cut. In this sense, from the application of different doses of urea was found, only significant effect of nitrogen on seed yield, so the addition of a unit of urea increased by 1.7 units seeds. Occurred relationship between levels of SPAD when the assessment was conducted before flowering. Prior to harvest seed regression models between SPAD and urea levels were not significant. The seed physiologic quality was not affected by the levels of in the soil seeds and urea.